Evolution and Population Dynamics of Clonal Complex 152 Community-Associated Methicillin-Resistant Staphylococcus aureus - Sharmin Baig (American Society for Microbiology, 2020)
ABSTRACT Since the late 1990s, changes in the epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) were recognized with the emergence of community-associated MRSA (CA-MRSA). CA-MRSA belonging to clonal complex 152 (CC152), carrying the small staphylococcal cassette chromosome mec (SCCmec) type V and encoding the Panton-Valentine leukocidin (PVL), has been observed in Europe. The aim of this study was to investigate its origin, evolution, and dissemination. Whole-genome sequencing was performed on a global collection of 149 CC152 isolates spanning 20 years (93 methicillin-susceptible S. aureus [MSSA] and 56 MRSA isolates). Core genome phylogeny, Bayesian inference, in silico resistance analyses, and genomic characterization were applied. Phylogenetic analysis revealed two major distinct clades, one dominated by MSSA and the other populated only by MRSA. The MSSA isolates were predominately from sub-Saharan Africa, whereas MRSA was almost exclusively from Europe. The European MRSA isolates all harbored an SCCmec type V (5C2&5) element, whereas other SCCmec elements were sporadically detected in MRSA from the otherwise MSSA-dominated clade, including SCCmec types IV (2B), V (5C2), and XIII (9A). In total, 93% of the studied CC152 isolates were PVL positive. Bayesian coalescent inference suggests an emergence of the European CC152-MRSA in the 1990s, while the CC152 lineage dates back to the 1970s. The CA-MRSA CC152 clone mimics the European CC80 CA-MRSA lineage by its emergence from a PVL-positive MSSA ancestor from North Africa or Europe. The CC152 lineage has acquired SCCmec several times, but acquisition of SCCmec type V (5C2&5) seems associated with expansion of MRSA CC152 in Europe. IMPORTANCE Understanding the evolution of CA-MRSA is important in light of the increasing importance of this reservoir in the dissemination of MRSA. Here, we highlight the story of the CA-MRSA CC152 lineage using whole-genome sequencing on an international collection of CC152. We show that the evolution of this lineage is novel and that antibiotic usage may have the potential to select for the phage-encoded Panton-Valentine leukocidin. The diversity of the strains correlated highly to geography, with higher level of resistance observed among the European MRSA isolates. The mobility of the SCCmec element is mandatory for the emergence of novel MRSA lineages, and we show here distinct acquisitions, one of which is linked to the successful clone found throughout Europe today.